2017
DOI: 10.31018/jans.v9i3.1446
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic variability and character association in okra genotypes for yield and contributing characters

Abstract: A study of genetic diversity in 20 okra genotypes for 22 morphological and agronomic traits (13 quantita- tive and 9 qualitative) was laid out in randomized block design with three replications during 2015-16. The phenotyp- ic and genotypic variances, phenotypic (PCV) and genotypic coefficients of variation (GCV), heritability, genetic ad- vance of the characters were studied. The genotypes demonstrated wide range of variability for all characters. In this study PCV was higher than its corresponding GCV thus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The moderate to lowest (<20) values were found in number of seeds per fruit (7.823), days to 50% flowering (5.749), days to first flowering (5.033), average fruit weight (3.416), number of nodes on main stem (3.394), number of fruits per plant (3.168), length of mature fruit (1.623), number of primary branches (0.742), internodal length (0.66), seed index (0.466), and diameter of fruit (0.21) from (Table3). similar findings were observed in [9].…”
Section: Genetic Advance and Genetic Advance As Percent Of Meansupporting
confidence: 90%
See 1 more Smart Citation
“…The moderate to lowest (<20) values were found in number of seeds per fruit (7.823), days to 50% flowering (5.749), days to first flowering (5.033), average fruit weight (3.416), number of nodes on main stem (3.394), number of fruits per plant (3.168), length of mature fruit (1.623), number of primary branches (0.742), internodal length (0.66), seed index (0.466), and diameter of fruit (0.21) from (Table3). similar findings were observed in [9].…”
Section: Genetic Advance and Genetic Advance As Percent Of Meansupporting
confidence: 90%
“…The moderate (10-20%) PCV were recorded respectively for number of fruits per plant (16.126), plant height (15.037), average fruit weight (14.609), number of nodes on main stem (11.472) and internodal length (10.845).The low (<10%) estimates of PCV were observed respectively for number of seeds for fruit (9.647), length of mature fruit (9.397), diameter of fruit (7.562), seed index (7.508), days to 50% flowering (6.745) and days to first flowering (6.328) from (Table 3). A similar declaration has been made by Rana et al, [8] and Kumari et al, [9].…”
Section: Genotypic and Phenotypic Variencementioning
confidence: 54%
“…The days to 50% flowering (r= 0.5294*, P<0.05) was found to be negatively correlated with okra yield as increasing days to 50% flowering significantly reduced the okra pod yield. These results also affirmed to Kumari et al (2017) who reported that delayed flowering reduced the yield traits in okra including canopy photosynthesis, conversion of assimilates to biomass and partitioning of assimilates to grain, and higher yield attributing traits . DOV-88 and Kashi Kranti was found to be best for traits, namely plant height, leaf width, pod diameter, pod weight and okra yield.…”
Section: Genotypic Variation On Growth and Yield Attributessupporting
confidence: 87%
“…Archana et al (2015) found a positive association between fruit length with plant height and no. of nodes plant -1 ; Kumari et al (2017) for average fruit weight and fruit yield plant -1 ; Reddy et al (2013) for no. of fruits plant -1 and no.…”
Section: Correlation Coefficient Analysismentioning
confidence: 99%